Information evaluation - Capet, Philippe; Delvallade, Thomas (London : ISTE, Ltd. ; Hoboken : Wiley, 2014)
"Spanning the approaches offered by philosophy, military intelligence, algorithmics and information science, this book presents the concepts of information and the confidence placed in it, the methods that militaries, the first to be aware of the need, have or should have adopted, tools to help them, and the prospects that they have opened up. Beyond the military context, the book reveals ways to evaluate information for the good of other fields such as economic intelligence, and, more globally, the informational monitoring by governments and businesses."--
Information: philosophical analysis and strategic applications -- Epistemic trust -- The fundamentals of intelligence -- Information evaluation in the military domain: doctrines, practices and shortcomings -- Multidimensional approach to reliability evaluation of information sources -- Uncertainty of an event and its markers in natural language processing -- Quantitative information evaluation: modeling and experimental evaluation -- When reported information is second hand -- An architecture for the evolution of trust : definition and impact of the necessary dimensions of opinion making.
Includes bibliographical references and index.
Print version record.
Keywords: Data integrity; Data integrity; Electronic books; Electronic books